Global Begins from Local: International Students and International Programs at Historically Black Community Colleges and Tribal Community Colleges (Comparative & International Education Series, 2021)
Chapter 14|13 pages Global Begins from Local: International Students and International Programs at Historically Black Community Colleges and Tribal Community CollegesBy Krishna BistaThis chapter offers an overview of international students and international education programs and initiatives at historically Black community colleges and tribal community colleges in the United States. This chapter also highlights the strengths and challenges of these community colleges and international programs. Building on their unique historical identities, heritage, and indigenous values of these institutions, the author argues that local is the beginning of global initiatives and draws some examples of exemplary community colleges that can be role model for other institutions.